2010
DOI: 10.1002/eji.200939759
|View full text |Cite
|
Sign up to set email alerts
|

A novel immunoregulatory function for IL‐23: Inhibition of IL‐12‐dependent IFN‐γ production

Abstract: Most studies investigating the function of IL-23 have concluded that it promotes IL-17-secreting T cells. Although some reports have also characterized IL-23 as having redundant pro-inflammatory effects with IL-12, we have instead found that IL-23 antagonizes IL-12-induced secretion of IFN-c. When splenocytes or purified populations of T cells were cultured with IL-23, IFN-c secretion in response to IL-12 was dramatically reduced. The impact of IL-23 was most prominent in CD8 1 T cells, but was also observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…IL-23 → IFN γ: The reverse situation was observed in regulation of IFNγ production by IL-23 in murine lymphocytes (Sieve et al 2010). IL-23 antagonizes IL-12-induced secretion of IFNγ.…”
Section: Structure Of Il-23 Cytokine and Regulation Of Secretionmentioning
confidence: 99%
“…IL-23 → IFN γ: The reverse situation was observed in regulation of IFNγ production by IL-23 in murine lymphocytes (Sieve et al 2010). IL-23 antagonizes IL-12-induced secretion of IFNγ.…”
Section: Structure Of Il-23 Cytokine and Regulation Of Secretionmentioning
confidence: 99%
“…It has been reported that IL‐23R signaling can influence Th1 polarization,17 indicating that loss of IL‐23R signaling in our study may have secondary effects. Although we cannot rule out any secondary effect on Th1 priming, levels of Th1 cells were similar in spleen and lymph nodes of mice lacking IL‐23R signaling compared with wild‐type mice.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast several previous reports have found a protective role of IL-17 in atherogenesis indicating a complex regulatory function of Th17 cells in various inflammatory conditions [10,11]. It has recently been shown that IL-23 can act as a negative regulator of IL-12 induced IFN-γ production and Th1 immunity independent of other Th17 cytokines [16]. This might imply that IL-23 is involved in pathogenesis of CAD by other mechanisms rather than Th17 cell expansion and regulation, which must be further investigated.…”
Section: Discussionmentioning
confidence: 82%